Aksesibilitas Petani Tomat Terhadap Sumber Pembiayaan di Kecamatan Arjasari Kabupaten Bandung - Rosdiani, Dian; Wulandari, Eliana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The agricultural sector has a crucial role in the national economy. The costs incurred in cultivating tomatoes are substantial, while the dynamics of rural agriculture, such as crop failures, pest and disease attacks, unpredictable climate changes, declining selling prices, and difficulties in obtaining fertilizers, create a cascade of new problems. One of the impacts is on the financial aspect, where tomato farmers may face challenges in initiating the next planting season if the previous harvest was insufficient. As an alternative solution, farmers can seek agricultural financing through various financial sources. Therefore, this research aims to analyze the experiences of tomato farmers in obtaining agricultural financing and the accessibility to financial sources in the Arjasari Sub-district. The study was conducted in the villages of Mekarjaya and Pinggirsari in the Arjasari Sub-district of Bandung District. Informants consisted of 9 tomato farmers with land size criteria categorized as follows: large category with the criteria of having land size more than 1 Ha, medium category with criteria 0.5 - 1 Ha, and small category with criteria less than 0.5 Ha. The data analysis method used was qualitative descriptive analysis applying a case study technique. The research results indicated that the factors influencing informant farmers in selecting financing sources were interest rates and loan conditions, loan amounts provided, repayment periods, and experience with financial sources. The accessibility of tomato farmers, considering availability, ease, sustainability, and flexibility dimensions of  financing is mainly through bank loans and assistance in the form of  loans from traders or middlemen.